Current status of immunoglobulin M seroprevalence in women with adverse reproductive outcomes in current pregnancy: experience in a teaching institution - Tiwari, Sana; Arora, Balvinder Singh; Sen, Poornima; Dewan, Rupali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: During pregnancy, the immune system is suppressed, making the individual susceptible to infections. One of the most common causes of perinatal mortality in developing countries is TORCH infections. Screening for TORCH agents during pregnancy identifies high risk mothers thereby providing the clinician with opportunity to intervene. Methods: A total of two hundred women with adverse pregnancy events in current pregnancy formed the study group while 150 women with normal pregnancy outcome formed control group. Presence of IgM antibodies against TORCH agents were detected by ELISA and results expressed qualitatively as positive or negative. Results: Our study revealed 45.56% women in current pregnancy were positive for IgM serology while in controls it was only 14.67 % (p value <0.0001). The percentage frequency of TORCH agents in terms of IgM seropositivity for toxoplasma was as 14.63%, 15.86% for rubella, 23.17% for CMV, 46.34% for HSV. Conclusions: It may not be possible to screen all patients with adverse reproductive outcome for TORCH but all women with adverse reproductive outcome in current pregnancy should be subjected to TORCH testing, especially to safeguard future pregnancies. The affected females should be counseled regarding continuation of pregnancy but remain under observation and treatment. Positive serology findings as supportive evidence to clinical diagnosis, if kept in consideration, may help manage future pregnancies more effectively.